A study of 10 years risk prediction of CAD – applying “Framingham risk scores” among the coal mine employees of the Singareni Collieries company ltd, Telangana state, India - Mahabhashyam, Ramakrishna Narashima; Singh, Sunil Pal; Carolin, Archana; Varaprasada, Maruti Sarma Mannava (International Journal Of Community Medicine And Public Health, 2017)
Background: Cardiovascular Disease (CVD) has become the leading cause of death. Many tools for CVD risk assessment have been devised. While it is relatively easy to identify those who are obviously at high risk, the health expenditure can be predicted and necessary high risk based preventive care programmes can be introduced. The study has been taken up with an objective of assessing “10 years risk prediction of CAD, Among the Coal Mine Employees by applying “Framingham Risk Scores.”. Methods: Study population: coal mine employees (30-60 years of age). Study area: Singareni Collieries Company Limited (SCCL), Telangana State, India. Study design: cross-sectional observational study. Sample size: 53367coal mine workers. Sampling methods: All coal mine employees (30-60 years) working atleast of 10 years duration and those who have given consent for the study have been included. Data collection: collected from the periodic medical examination records from 2008 to 2012. Analysis: By using Micro soft Excel 2007 and SPSS version 19. Results: Majority of the workers were in the age group of 51-60 years of age, followed by 41-50 years (31.5%). 11.9% has mild risk, 3.2% has moderate risk and 0.6% has severe risk of CAD. Mining Surface labourers has marginally higher risk of CAD than “Mining Supervisory and Managerial Staff’, Opencast mining staff were found to at higher risk of CAD. Conclusions: Mining Surface labourers and opencast mining staff were found to at higher risk of CAD.